Determinan kualitas laporan keuangan pemerintah daerah - indra kurniawan (KINERJA, 2016)
Preparation and financial reporting is an obligation that is done for every organization both private sector and public sector. This is because the financial statements serve as a benchmark to see if the performance is happening in an institution can run well and properly. This study was conducted to see the determinant in creating a higher quality financial statements because one of the requirements for a financial statement is to have adequate information and can dipahmi for each user, so that in the preparation of financial statements should be more attention to several contributing factors. In this study, trying to see what factors can influence the creation of a higher quality financial statements so as to facilitate its user. This study uses three factors that are considered to influence the improvement of the quality of the financial statements of the competence of local government human resources, utilization of information technology, as well as the internal control system within the organization which will then be processed with the help of statistical programs in the form SmsrtPLS. After testing the analysis of the three factors used in this study by using analytical tools SmartPLS result that the competence of human resources has a positive and significant impact on the quality of financial reports of local government, it can be seen from the value of t obtained which is equal to 5, 254,386. So it may be indicated that the greater the competence of an employee can impact the quality of financial reporting. As for the use of information technology factors also influence a positive and significant impact on improving the quality of local government financial statements which can be seen from the value t obtained which is equal to 2.201480. As for the internal control system has no effect on the quality of government financial statements it can be seen from the values obtained by 0.977357. And the third factor to use significant benchmark by 1.96.Keywords: quality of financial reporting, internal control systems,human resource competencies,.